Capillaroscopic findings in a case of Hajdu-Cheney syndrome. Issue 3 (March 2016) - Damian, L.-O.; Simon, S.-P.; Filipescu, I.; Bocsa, C.; Botar-Jid, C.; Rednic, S.
Abstract Summary Hajdu-Cheney syndrome (HCS) is a rare disease which causes osteoporosis, digit shortening, and early tooth loss. In a young HCS female patient, the nailfold capillaroscopy showed reduced capillary height and reduced density in all affected fingers. Capillaroscopy could improve follow-up and therapy assessment in HCS. Hajdu-Cheney syndrome (HCS) is a very rare connective tissue disease characterized by osteoporosis, early dentition loss and a particular phenotype as a result of enhanced NOTCH2 signaling. The pathogenesis of bone resorption and osteoporosis is not fully understood. The altered angiogenesis may play a role in acroosteolysis. We performed capillaroscopy in order to assess the microvascular involvement in a 21-year-old female patient with sporadic HCS. The patient presented with severe parodontopathy, acroosteolysis, and clubbing of four fingers and three toes. Hand radiographs showed periarticular osteoporosis and asymmetric bony involvement with acral resorption and/or transversal lucency bands in several fingers. Early collagen-vascular diseases were ruled out by clinical and ancillary examinations, including immunology and immunoblot for systemic sclerosis. Nailfold capillaroscopy showed reduction of capillary height and density in all affected fingers. Notably, in the fingers with acral resorption, many capillaries were dilated, while in the ones with radiolucency band, capillary dilation was a rare finding. In clinically unaffected fingers, the capillaroscopic findings were normal.To our knowledge, this is the first report of capillaroscopic findings in HCS. The nailfold capillaroscopic aspect reflects the involvement of acral vessels in HCS; thus, capillaroscopy may represent an early diagnostic tool as well as a means of therapeutical assessment. Repeated capillaroscopy in HCS may also add to the understanding of its pathogenesis.